Encourging student motivation in junior high school by developing virtual field trip - Abidin, Mohammad Yusril; Wahyuningtyas, Neni (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
This research aims to develop Virtual Field Trip (VFT) learning media to increase students' learning motivation regarding natural resource use in 8th grade. This media was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development of 360-degree panoramic image-based VFT media is expected to overcome the limitations of conventional learning. The study was conducted on 32 8th-grade students at SMPN 7 Malang using a one-group pretest-posttest design. The analysis showed a significant increase in students' learning motivation, with the average pretest score increasing from 59 to 80.2 in the posttest. The t-test showed a significant value of 0.000, meaning that VFT media significantly affects learning motivation. These media have been proven to grab students' attention, facilitate understanding of the material, and provide a contextualized learning experience. Although there are barriers, such as the need for Internet connectivity and devices, the results of this study underscore the importance of innovation in learning media to increase student engagement.